What factors cause foreign banks to stay in London? - Clare, A.; Gulamhussen, M. A.; Pinheiro, C. (Journal of International Money and Finance, 2013)
The banking literature focuses extensively on the phenomenon of bank entry and pays less attention to the factors driving the continuation of banking activities in foreign markets. In this paper, we analyze this important, but overlooked, issue by constructing a unique database of foreign banks that continue operating and those that have withdrawn from arguably the world's most international banking center-London. This new data set comprises information on 408 offices from 77 countries spanning the period from 1945 to 1999, giving us 4643 observations, of which 2795 represent offices that continue operating and 1848 that withdrew from London during this period. Our empirical work shows that the continuation of international banking activity in London is positively related to: the setup of locally integrated organizational forms at entry; the experience in the local market; and the size of local operations. Continuation of banking activities is however negatively related to the setup of organizational forms integrated into the parent bank at entry and to the geographic distance of the home-country to London. We also find that higher global economic activity increases the likelihood of international banking operations continuing in London; however, the more volatile the global economic environment, the greater the prospect of a cessation of this activity.